Justice over the Course of Life Biographies in a Society of Long Lives - Schmitz-Luhn, Björn; Woopen, Christiane (Schriften zu Gesundheit und Gesellschaft - Studies on Health and Society, 2022)
IX, 127 p. 15 illus., 8 illus. in color.